PENERAPAN ALGORITMA C4.5 UNTUK MENENTUKAN REWARD KARYAWAN PADA PT INDOLAND BATAM - kok seng, vincent kiu; Harman, Rika (LPPM Universitas Putera Batam, 2021)
In the face of intense competition due to technological changes and environmental changes in various areas of life, all companies are looking for employees who have the potential to provide the best and useful services. In this way, the company can not only provide satisfactory service (customer satisfaction), but also embody value (customer value). Operating companies not only pursue productivity but also performance. PT Indoland Batam is a company engaged in online sales or an online shop that provides items such as household appliances, bags, shoes, beauty tools, clothes, and so on. This company was founded in 2017, which is located at Citra Buana Park 1, Blok H No 2, Jalan Yos Sudarso, Kampung Seraya Batam. In determining the reward for employees in the company, there are many obstacles or problems that the company must face, including time efficiency, many comparisons of the variables tested, and decision making to determine the employee's reward. As the years passed, employees at PT Indoland Batam were often dissatisfied with the reward they received, so this problem resulted in underperformance of employees, employee discipline, and employee loyalty to PT Indoland Batam.